Maximizing Millennial Students Role in Combating COVID-19 Hoaxes and Myths - Astri Dewayani; Euvanggelia Dwilda Ferdinandus; Rizki Putra Prastio; Indah Fahmiyah; Amila Sofiah; Rodik Wahyu Indrawan; Mochammad Nurul; Gagas Gayuh Aji; Nanda Rachmad Putra Gofur; Siti Khaerunnisa; Dewi Sriani; Yankel Sena (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2021)
Introduction: Since the outbreak of Corona Disease-19 (COVID-19) spreads all over the world, various ways of health attempts have been conducted. However, overflowed information intertwines with mis/disinformation could raise public anxiety and stigma-related diseases. We aimed to assess the help of the young generation of millennials and Gen-Z whom are active college students in debunking hoaxes and myths of COVID-19 into their community.Method: The selected students were given a short course on COVID-19 basic information, prevention, and circulated myths. Later, they become ambassadors and actively educated via offline and online platforms. The impact of outspread information on audiences was investigated through a qualitative survey.Result: The knowledge of students were measured by pre- and post-test within the short course. Prior knowledge showed the least understanding part was prevention and myth of COVID-19. There was a significant improvement of knowledge in post-test after receiving seminar (p=0.0002). There were 97 respondents who filled the online survey that predominantly in young adulthood age. Respondent's insight was enhanced and they likely intend to spread the actual information to their surroundings.Conclusion: Appointing student as the spokesperson for health education can raise their social responsibility. Clarifying misinformation and health behaviour could be more influential within the same sharing community. In addition, the use of various online platforms could efficiently reach massive target, especially young ages.